2017
DOI: 10.1002/2017ja023911
|View full text |Cite
|
Sign up to set email alerts
|

Quiet and Disturbed Time Characteristics of Blanketing Es (Esb) During Solar Cycle 23

Abstract: A sporadic E layer with dense ionization blocks the upper ionospheric layers in ionosonde observations and it is called, blanketing sporadic E (Esb). Although earlier studies have demonstrated that Esb occurrence is dependent on solar activity, seasons, local time, and equatorial electrojet/counter equatorial electrojet (EEJ/CEEJ) strength, the physics behind this dependence is not well established particularly at the dip equatorial stations. Moreover, fewer comprehensive studies are available on Esb. Present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Another current system is the EEJ, which is an eastward current flowing in a narrow latitudinal belt (±3°) over the magnetic equator in the E-region. The hourly values of horizontal component of the ground magnetic field (H) recorded at Alibag and Tirunelveli/Trivandrum are used to estimate the strength of EEJ on nth day at local time t = 1-24 as follows (Yadav et al, 2017):…”
Section: Data Sets and Energy Estimatesmentioning
confidence: 99%
“…Another current system is the EEJ, which is an eastward current flowing in a narrow latitudinal belt (±3°) over the magnetic equator in the E-region. The hourly values of horizontal component of the ground magnetic field (H) recorded at Alibag and Tirunelveli/Trivandrum are used to estimate the strength of EEJ on nth day at local time t = 1-24 as follows (Yadav et al, 2017):…”
Section: Data Sets and Energy Estimatesmentioning
confidence: 99%
“…Sporadic-E manifests itself as a non-uniform, wavy layer, or a composition of irregular elongated clouds of intense ionization within the lower E-region of the ionosphere [1,4]. There are many methods and instruments used to monitor sporadic-E including incoherent scatter radars (ISRs) [5], ionosondes [6][7][8][9][10], and GPS radio occultation (RO) [11,12]. While ISR measurements provide detailed E s observations, the number of sites across the globe are significantly lacking for global climatological studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is quite expected. The previous studies using GPS RO (Arras et al, 2008;Chu et al, 2014;Wu et al, 2005;Yu et al, 2019) and ionosonde measurements (Jo et al, 2019;Yadav et al, 2017;Zhou et al, 2017) reported this summer maximum dependence. Haldoupis et al (2007) explained this seasonal behavior in terms of the maximum meteor influx during summer in the Northern Hemisphere.…”
Section: Statistical Characteristics Of the Es B Layersmentioning
confidence: 66%
“…The occurrences of Es b layers have been studied on a global scale using satellite data (Arras & Wickert, 2018; Chu et al., 2014; Luo et al., 2021; Wu et al., 2005; Yu et al., 2019; Yue et al., 2016) and overhead at some ionospheric stations with ground‐based radar such as ionosondes (Abdu et al., 1996; Andrioli et al., 2022; Conceição‐Santos et al., 2019; Jo et al., 2019; Pignalberi et al., 2014; Resende et al., 2017b; Yadav et al., 2017; Zhou et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation